Longing for which home: Evidence from global aspirations to stay, return or migrate onwards - Els Bekaert; Amelie F. Constant; Killian Foubert; Ilse Ruyssen (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2021)
Aspirations provide the underlying dynamics of the behavior of individuals whether they are realized or not. Knowledge about the characteristics and motives of those who aspire to leave the host country is key for both host and home countries to formulate appropriate and effective policies in order to keep their valued immigrants or citizens and foster their (re-)integration. Based on unique individual-level Gallup World Polls data, a random utility model, and a multinomial logit we model the aspirations or stated preferences of immigrants across 138 countries worldwide. Our analysis reveals selection in characteristics, a strong role for soft factors like social ties and sociocultural integration, and a faint role for economic factors. Changes in circumstances in the home and host countries are also important determinants of aspirations. Results differ by the host countries' level of economic development.
Keywords: J15; J61; J68; D01; F22; C55; O15; 330; Economics of Immigrants; Geographic Labor Mobility; Public Policy; Micro-economic Behavior; International Migration; Large Data Sets; Modeling and Analysis